Very high-speed running (VHSR) profile in elite female football: An update - Olaizola, A.; Errekagorri, I.; Lopez-de-Ipina, K.; Calvo, P. M.; Castellano, J. (PLOS ONE, 2024)
The aim of the present study it`s a providing an update of the profile of very high-speed running (VHSR) of professional female football players. In this study 23 official matches of the Spanish First Division of Women´s Football were analysed. A total of 15 players participated, who were classified according to their location on the matches played: central-corridor (CCP, n = 7), and lateral-corridor (LCP, n = 8). The variables recorded were: 1) Very High-Speed Running (VHSR), considering the accumulated distance, duration, and frequency, and the individual characteristics of the efforts (distance and duration); 2) Recovery between efforts (VHSRe) and; 3) VMAX. The results show that LCP described higher values in accumulative VHSR and VHSR by distance bands, with greater distances, durations and VMAX of VHSRe, with less recovery between efforts. There seems to be an evolutionary trend in the distribution of the efforts, with a higher % of efforts in the 10-20 m band. The results provide useful information that coaching staff of professional women`s football teams could use to design specific very high-speed running training to optimize performance in competition.